High UV-visible photocatalytic activity of Ag3PO4dodecahedral particles synthesized by a simple hydrothermal method - Saowalak Krungchanuchat (2018)
© 2017 Elsevier B.V. Silver phosphate (Ag3PO4) was successfully synthesized in the solutions with pH of 8 by a hydrothermal method at 100–200 °C and a precipitation method at room temperature (ca 32 °C) without any surfactant adding. Phase, morphology and vibrational modes of the products were characterized by XRD, FE-SEM and FTIR. Only morphology and crystalline degree were controlled by the synthetic methods and conditions. In this research, Ag3PO4was found to have the potential in photocatalytic degradation of organic rhodamine B (RhB) dye molecules. The photocatalytic activity of Ag3PO4dodecahedral particles synthesized by the 150 °C and 24 h hydrothermal reaction has the highest activity of 99.55% in decolorizing of RhB under UV light within 120 min.